Early agropastoral settlement and cultural change in central Tibet in the first millennium BC: excavations at Bangga. (August 2021) - Lu, Hongliang; Chen, Xinzhou; Zhang, Zhengwei; Tang, Li; Lemoine, Ximena; Wangdue, Shargan; Chen, Zujun; Liu, Xinyi; Frachetti, Michael D.
Abstract : Abstract : Archaeological research demonstrates that an agropastoral economy was established in Tibet during the second millennium BC, aided by the cultivation of barley introduced from South-western Asia. The exact cultural contexts of the emergence and development of agropastoralism in Tibet, however, remain obscure. Recent excavations at the site of Bangga provide new evidence for settled agropastoralism in central Tibet, demonstrating a material divergence from earlier archaeological cultures, possibly corresponding to the intensification of agropastoralism in the first millennium BC. The authors' results depict a more dynamic system of subsistence in the first millennium BC, as the populations moved readily between distinct economic modes and combined them in a variety of innovative ways.